2016
DOI: 10.1002/polb.24226
|View full text |Cite
|
Sign up to set email alerts
|

Influence of graphene oxide incorporation and chemical cross-linking on structure and mechanical properties of layer-by-layer assembled poly(Vinyl alcohol)-Laponite free-standing films

Abstract: Functional fillers in multilayered films provide opportunity in tailoring the mechanical properties through chemical cross‐linking. In this study, Laponite‐graphene oxide co‐dispersion was used to incorporate graphene oxide (GO) easily into polyvinyl alcohol (PVA)/Laponite layer‐by‐layer (LBL) films. The LBL films were found to be uniform and the layer thickness increased linearly with number of depositions. The process was extended to a large number of depositions to investigate the macroscopic mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Moreover, few more peaks were observed at 509.7 and 836.2 cm −1 , which could be attributed to a phase β of PVDF‐HFP . In addition, the OH stretching of H‐bonding and CH stretching appears at 3300–3500 cm −1 and 3000 cm −1 that confirms the successful modification of PVDF‐HFP/CNF with glutaraldehyde crosslinked with collagen …”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Moreover, few more peaks were observed at 509.7 and 836.2 cm −1 , which could be attributed to a phase β of PVDF‐HFP . In addition, the OH stretching of H‐bonding and CH stretching appears at 3300–3500 cm −1 and 3000 cm −1 that confirms the successful modification of PVDF‐HFP/CNF with glutaraldehyde crosslinked with collagen …”
Section: Resultsmentioning
confidence: 67%
“…MD laboratory‐scale system was utilized by considering NaCl aqueous solution of 30 g/L concentration as the feed stream solution. As per our previous studies, the feed stream solution temperature has been maintained at 70 °C in a hot‐water bath, whereas the cold permeate side was controlled at 20 °C by re‐circulating distilled water . It was observed that the effective membrane area was 100 cm 2 (with specifications: 10 cm × 10 cm).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This membrane was superficially modified immersing it alternately in PEI and GA solutions. The spectra of both modifying solutions are shown after the AEM (panels d and e), along with their principal peaks [55,56,57,58]; finally, panel f presents the spectrum for the modified-AEM. The GA can react with the primary and secondary amines of the PEI; this process allows the assembling of the subsequent PEI layers [41,59].…”
Section: Results and Discussionmentioning
confidence: 99%
“…Their remarkable reactivity results in a high crosslinking density, reducing thus considerably the free volume in the film. Other than the gas barrier, crosslinking improves also the mechanical properties [10] due to the modification of the polymer structure with the established covalent bonds [11]. The acetal formation and crosslinking reaction is known to be reversible, which could be avoided with acidic conditions.…”
Section: Introductionmentioning
confidence: 99%